GALT Deficiency Galactosemia. Issue 1 (January 2018) - Anderson, Sharon
Abstract : Abstract: Galactosemia is an inborn error of galactose metabolism that results from a deficiency in one of three enzymes, uridine diphosphate galactose 4'epimerase, galactokinase, or galactose-1-phosphate uridyltransferase (GALT). This article focuses on classical, clinical variant, and biochemical variant (Duarte) galactosemias caused by GALT enzyme deficiency. A brief overview of galactosemia and newborn screening is presented, followed by detailed information about each of the conditions. Confirmatory testing, acute and long-term management, and outcome for these galactosemia types are discussed as well as the importance of genetic counseling and testing for the infant and family to refine reproductive risk. Abstract : Galactosemia is an inborn error of galactose metabolism that results from a deficiency in one of three enzymes. This article focuses on classical, clinical variant and biochemical variant (Duarte) galactosemias. Confirmatory testing, acute and long-term management, and outcomes for these galactosemia types are discussed, as well as the importance of genetic counseling and testing for the infant and family to refine reproductive risk.